Supervision of the Regional Inspectorate of North Sulawesi Province on the Implementation of City District Government Affairs - Julieta N. Rumawir,; Steven V. Tarore,; Lidya Tengker,; Nixon J. Sindua,; Ida Bagus Weda Wigena, (Technium Social Sciences Journal, 2024)
This study aims to analyze and describe the implementation of the Regional Government Affairs Supervision Program. The research method used is descriptive qualitative method. The results showed that supervision of the implementation of local government affairs in the Annual Supervision Work Program (PKPT) has not been running well until now. This can be explained through the following three indicators: 1. The Role of Government Internal Supervisory Apparatus (APIP) In the context of supervision carried out by the Inspectorate of North Sulawesi Province on the implementation of City Government affairs, the role of APIP has not been fully realized in the form of examination. In other words, the supervisory function has not been carried out in accordance with the applicable standard operating procedures (SOP), so that the supervisory process is not running well. 2. The Implementation of the Supervision Program, the implementation of the Supervision Program has not been running effectively until now, one of which is due to the COVID-19 pandemic. This pandemic has resulted in a refocusing of budgets and face-toface meetings, so that inspection priorities are more focused on the scope of the provincial government and have not reached the government at the district / city level. 3. Program Effectiveness: The implementation of the Annual Supervision Work Program (PKPT) has not been fully effective. Most of the programs in the PKPT have not been implemented and realized properly. There are still various inhibiting factors that result in the non-optimality of the implementation of this program, one of which is the limitations in supervising the implementation of government affairs at the district/city level.